Identification of Mangrove Density from 2014 to 2024 using Landsat 8 at Clungup Mangrove Conservation (CMC) Tiga Warna South Malang Coast - Budianto, Nada Rafila; Wahyuni, Sri; Jumriati, Jumriati; Arsyad, Muhammad; Saputra, Aswin Nur (JPG (Jurnal Pendidikan Geografi), 2025)
Mangroves are very important ecosystems for coastal environments because they function as natural protection against coastal erosion, reduce high waves, and provide habitat for various marine species. This study aims to identify changes in mangrove density between 2014 and 2024 in Clungup Mangrove Conservation (CMC) Tiga Warna, South Malang coast, East Java. The methods used included data collection, data pre-processing, data processing, temporal analysis, and data validation using Landsat 8 satellite imagery. The results showed that mangrove density increased significantly over a 10-year period. In 2014, the area with high density only reached 19,110 ha, while in 2024 it increased to 50,194 ha. Spatially, areas with high density categories expanded by 10%, while areas with low density categories decreased by 5%. These changes indicate the success of rehabilitation and conservation programs that have been carried out, and highlight the importance of community involvement in maintaining mangrove ecosystems.